Tales of Dune - Herbert, Brian; Anderson, Kevin J., 1962- (Herbert, Frank. Dune series., 2022)
Frank Herbert's magnificent Dune saga sprawls across countless planets and tens of millennia...But while the main novels concentrate on major events and major characters, a universe this complex begs for additional stories, filing in all the details that may sometimes get overlooked in the telling of the main saga. Tales of Dune collects eight such stories, ranging from the period of the Butlerian Jihad, to the time of young Paul Atreides, to a story set during the events of the novel Dune, to the very end of Frank Herbert's future history."--Dust jacket flap.